Heat Stress And Outdoor Workers In Nigeria: An Examination Of Risks And Coping Mechanisms - Surajo, Aminu Zubairu (Economics, Business, Accounting & Society Review, 2024)
This study investigates the impact of heat stress on the health and productivity of outdoor workers in Kano, Nigeria, a region increasingly affected by rising temperatures due to climate change. Outdoor occupations such as construction, street vending, transport, agriculture, and security are particularly vulnerable to heat stress, posing significant occupational health risks and potential productivity losses. The study aimed to (1) identify factors contributing to heat stress, (2) examine associated health risks, and (3) evaluate coping mechanisms adopted by workers. A mixed-methods design was adopted, combining quantitative data from 217 respondents selected through simple random sampling and qualitative insights from 30 purposively selected interviewees. Findings revealed that while no significant relationship exists between the intensity of heat stress and worker productivity, prolonged exposure to direct sunlight, inadequate hydration, lack of rest breaks, and poor ventilation are key contributing factors. Health risks include dehydration, heat-related illnesses, exacerbation of chronic conditions, and increased likelihood of accidents. Though productivity effects were not statistically significant, respondents reported reductions in performance, absenteeism, and economic implications. The study identified hydration practices, work-rest cycles, use of shade, appropriate clothing, and heat-awareness training as common coping mechanisms. The implications of this research highlight the urgent need for targeted occupational health interventions, climate-adaptive labor policies, and investment in protective infrastructure to ensure outdoor worker resilience amid escalating environmental heat risks.